2011
DOI: 10.1007/s00062-011-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Spine in a Patient with Decompression Sickness

Abstract: The case of a 60-year-old male patient who was admitted to hospital because of a scuba diving accident is reported. The patient initially complained about dizziness and pain in the shoulders. The exact rate of ascent from diving was not known, however, the patient said that he had had a panic attack and went up very fast from a depth of at least 15 m. despite a rapid recompression the patient developed hypesthesia of the right upper limb 2 days later. To rule out a stroke magnetic resonance imaging (MrI) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This facilitating effect of the development of DCS, related to the right-to-left shunt, has also been suggested in some cases in breath-hold divers [ 14 ]. On the other hand, in DCS affecting the spinal cord, injury is thought to involve obstruction and congestion of venous drainage, in addition to direct injury by bubble formation within the cord itself [ 5 , 8 , 9 , 15 ]. Finally, in the case of neurological involvement of breath-hold diving-related DCS, knowledge of the pathophysiology is even less well understood, as this is a rarer pathology, with most published work on acute DCS in scuba divers and fewer reports on DCS in breath-hold diving [ 4 , 7 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This facilitating effect of the development of DCS, related to the right-to-left shunt, has also been suggested in some cases in breath-hold divers [ 14 ]. On the other hand, in DCS affecting the spinal cord, injury is thought to involve obstruction and congestion of venous drainage, in addition to direct injury by bubble formation within the cord itself [ 5 , 8 , 9 , 15 ]. Finally, in the case of neurological involvement of breath-hold diving-related DCS, knowledge of the pathophysiology is even less well understood, as this is a rarer pathology, with most published work on acute DCS in scuba divers and fewer reports on DCS in breath-hold diving [ 4 , 7 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Second, several histopathologic studies have demonstrated venous obstruction and white matter congestion. 45,46 Third, vasogenic edema, appearing as high signal on both DWI and ADC maps, was observed by Vollmann et al in 2011 47 in a case of spinal cord decompression sickness, also suggesting a venous rather than arterial pathologic process.…”
Section: Figmentioning
confidence: 90%
“…48,49 Authors of MR imaging studies of decompression illness frequently report that the different clinicoradiologic patterns mentioned above overlap in the same patient, thereby suggesting that no single unifying pathophysiologic mechanism could completely explain this complex condition. 14,16,47 Some have argued that there is a greater participation of arterial occlusion in brain lesions because they are more frequently described in cases of arterial gas embolism, while venous occlusion may play a greater role in spine lesions and may even be favored by local mechanical cord compression. 11,15 Whatever the preponderant mechanism involved, the treatment is urgent hyperbaric therapy to allow nitrogen to dissolve and be expelled via the lungs.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation